2018
DOI: 10.3174/ajnr.a5510
|View full text |Cite
|
Sign up to set email alerts
|

Development of High Signal Intensity within the Globus Pallidus and Dentate Nucleus following Multiple Administrations of Gadobenate Dimeglumine

Abstract: BACKGROUND AND PURPOSE:Previous studies have evaluated various gadolinium based contrast agents and their association with gadolinium retention, however, there is a discrepancy in the literature concerning the linear agent gadobenate dimeglumine. Our aim was to determine whether an association exists between the administration of gadobenate dimeglumine and the development of intrinsic T1-weighted signal in the dentate nucleus and globus pallidus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…Multiple subsequent studies have shown that such T1-dependent signal intensity changes persist in patients who have received repeated injections of the linear GBCAs, but repeated use of the macrocyclics results in minimal to no persistent change. [3][4][5][6][7][8][9][10][11][12] To explain these findings, studies have evaluated the entry into and clearance of contrast agents from the brain. [13][14][15][16] Experiments in rats provide evidence that the linear agents dissociate gadolinium from their chelate, which precipitates or binds to macromolecules and persists long-term within brain tissue.…”
mentioning
confidence: 99%
“…Multiple subsequent studies have shown that such T1-dependent signal intensity changes persist in patients who have received repeated injections of the linear GBCAs, but repeated use of the macrocyclics results in minimal to no persistent change. [3][4][5][6][7][8][9][10][11][12] To explain these findings, studies have evaluated the entry into and clearance of contrast agents from the brain. [13][14][15][16] Experiments in rats provide evidence that the linear agents dissociate gadolinium from their chelate, which precipitates or binds to macromolecules and persists long-term within brain tissue.…”
mentioning
confidence: 99%
“…17,18 However, concerns have recently been raised about brain deposition of the small-molecule Gd chelates currently used in clinical practice. 19,20 Compared with commercial small-molecule Gd chelate complexes, Gd-based inorganic nanoparticles (NPs) incorporate Gd 3+ ions into a solid structure rather than into organic molecules, effectively avoiding the possibility of dissociation and the consequent leakage of Gd 3+ while minimizing related toxicity and increasing the proton relaxivity. 21 A series of inorganic Gd-based compounds have been used for MRI contrast enhancement, including gadolinium oxides (Gd 2 O 3 ), 22,23 gadolinium fluorides (GdF 3 , NaGdF 4 ), 2426 gadolinium hydroxides (Gd(OH) 3 ), 27 and gadolinium oxysalts (GdVO 4 , GdPO 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…Most of the available reports on different rare earth (RE) orthovanadate nanomaterials have focused on the YVO 4 and LaVO 4 platforms. Because of the lackness of significant magnetic characteristics, the nanophosphors have been used only for biomedical applications, but they have not been used as MRI CAs . Actually, gadolinium vanadate (GdVO 4 ) is an essential host matrix, which is widely used in near-infrared (NIR) light and activated RE oxide phosphors. , However, concerns have recently been raised about brain deposition of the small-molecule Gd chelates currently used in clinical practice. , Compared with commercial small-molecule Gd chelate complexes, Gd-based inorganic nanoparticles (NPs) incorporate Gd 3+ ions into a solid structure rather than into organic molecules, effectively avoiding the possibility of dissociation and the consequent leakage of Gd 3+ while minimizing related toxicity and increasing the proton relaxivity . A series of inorganic Gd-based compounds have been used for MRI contrast enhancement, including gadolinium oxides (Gd 2 O 3 ), , gadolinium fluorides (GdF 3 , NaGdF 4 ), gadolinium hydroxides (Gd­(OH) 3 ), and gadolinium oxysalts (GdVO 4 , GdPO 4 ). Furthermore, in multifunctional imaging fields, these NPs are promising vehicles for carrying luminescence-imaging cations, especially trivalent lanthanide ions (Ln 3+ ).…”
Section: Introductionmentioning
confidence: 99%
“…Although, this effect is stronger after injections of linear ionic GBCAs than linear nonionic GBCAs (e.g. gadobenate dimeglumine) [913], signal intensity increases in case of both contrast agents [10, 14]. This phenomenon is rarely observed after repeated administration of macrocyclic GBCAs, except few recently published studies on pediatric population [4, 8, 9, 11, 12, 15].…”
Section: Introductionmentioning
confidence: 99%